The principle of equality and the problem of the permissibility of granting the children of Libyan women married to foreigners the Libyan nationality (Journal of Human Sciences, 2022)
The research deals with the issue of the principle of equality and the problem of the permissibility of granting the children of Libyan women married to foreigners the Libyan nationality. The research problem is summarized in answering the following main question: Why does the Libyan Nationality Law not give a Libyan mother married to a non-Libyan the right to grant her nationality to her children? Accordingly, the spatial boundaries of the research are limited to Libya, and the time limits extend from 2010 AD, due to the issuance of the Libyan Nationality Law No. 24 of 2010 AD, and the research stops at 2021, due to the issuance of the decision of the Prime Minister of the Interim Government of National Unity No. 332 of 2021 AD, regarding the formation of a central committee To study applications for obtaining Libyan citizenship and to prove the validity of belonging to Libyan origin, And that the general objective of the research is to try to reveal the extent of commitment to the principle of equality in international charters and agreements of which Libya is a key member, the interim constitutional declaration, and the reality of the enforcement of Law No. 24 of 2010, regarding Libyan nationality. The descriptive approach was adopted through the use of the legal approach and the political culture approach to achieve systematic integration, and according to the research questions and objectives, it was divided into an introduction and four demands: the first requirement deals with the principle of equality and the link with some other concepts, while the second requirement studies the reality of commitment to the principle of equality In mixed marriage, the third requirement focuses on nationality and the adoption of maternal lineage, and the fourth requirement deals with the role of political culture in consolidating the principle of equality. Accordingly, several results have been reached, the most important of which are: The principle of equality includes several political, economic and social fields, and that nationality is a right of man that entitles him to exercise his civil and political rights. The generally accepted law regarding the regulation of nationality provisions. And that the failure to activate the national number of the Libyan wife married to a foreigner led to her depriving her of the right to political participation in the elections of the Constitution Drafting Assembly and the Libyan Parliament in 2014. As for the recommendations, they are summarized in: Reviewing the laws and legislations related to the marriage of Libyan women married to non-Libyans, so as to put in place legislation and laws that preserve the dignity and rights of Libyan women married to non-Libyans, and their children, and respond to international conventions and conventions on human rights, with the need to work on activating the national number for Libyan women married to non-Libyans. Non-Libyans, in order to realize the principle of equality in political and civil rights.